First-principles investigations of electronic structures and optical spectra of wurtzite and sphalerite types of ZnO1-xSx (x=0, 0.25, 0.50, 0.75 &1) alloys. (January 2021) - Shabbir, Saira; Shaari, A.; Ul Haq, Bakhtiar; Ahmed, R.; AlFaify, S.; Ahmed, M.; Laref, A.
Abstract: Alloying of the zinc oxide (ZnO) with sulfur (S) chalcogen reveals vivid modifications of its electronic and optical properties driven by the dramatic restructuring of electronic structure. Here, we systematically executed mutual alloying of ZnO and ZnS in two different structural phases namely the wurtzite and sphalerite phases. Evolution in the physical properties of the designed ZnO1- x S x alloys for the compositions, x  = 0, 0.25, 0.50, 0.75 and 1 has been comprehensively examined by using full-potential linearized augmented-plane-wave plus local orbital approach within density functional theory. It is observed that the replacement of the Oxygen by Sulfur atoms significantly affects the band-structure profiles of ZnO1- x S x alloys in both wurtzite and sphalerite geometries. Furthermore, by increasing the S contents in ZnO1- x S x alloys, the conduction band minimum is found to be moved in the upward direction resulting in enhancement of the bandgaps. The electronic bandgaps of ZnO1- x S x alloys were enhanced from 2.65 eV to 3.68 eV in wurtzite and from 2.50 eV to 3.60 eV in sphalerite phase. Similarly, the imaginary parts of the dielectric function of ZnO1- x S x move towards a high energy regime with an increase in S composition, which resulted in a blueshift in their absorption edges. Our results are found well-matching with available theoretical and experimental results. The variation in the energy bandgaps and optical properties makes the S-rich ZnO a promising candidate for ultraviolet photoelectronic devices.